Territorial Stigmatisation and Poor Housing at a London ‘Sink Estate’ - Watt, Paul ca. 20./21. Jh. (Social Inclusion, 2020)
This article offers a critical assessment of Loic Wacquant’s influential advanced marginality framework with reference to research undertaken on a London public/social housing estate. Following Wacquant, it has become the orthodoxy that one of the major vectors of advanced marginality is territorial stigmatisation and that this particularly affects social housing estates, for example via mass media deployment of the ‘sink estate’ label in the UK. This article is based upon a multi-method case study of the Aylesbury estate in south London—an archetypal stigmatised ‘sink estate.’ The article brings together three aspects of residents’ experiences of the Aylesbury estate: territorial stigmatisation and dissolution of place, both of which Wacquant focuses on, and housing conditions which he neglects. The article acknowledges the deprivation and various social problems the Aylesbury residents have faced. It argues, however, that rather than internalising the extensive and intensive media-fuelled territorial stigmatisation of their ‘notorious’ estate, as Wacquant’s analysis implies, residents have largely disregarded, rejected, or actively resisted the notion that they are living in an ‘estate from hell,’ while their sense of place belonging has not dissolved. By contrast, poor housing—in the form of heating breakdowns, leaks, infestation, inadequate repairs and maintenance—caused major distress and frustration and was a more important facet of their everyday lives than territorial stigmatisation. The article concludes by arguing that housing should be foregrounded, rather than neglected, in the analysis of the dynamics of urban advanced marginality.